Peranan Regulasi Emosi terhadap Perundungan Siber pada Siswa SMA di Jakarta - Azzalea Djingga; Melita Kristi Delia; Stevi Tessanika Christy; Azahra Putri; Rita Markus Idulfilastri (Jurnal Ilmiah Wahana Pendidikan, 2023)
The emotional development of adolescents in the period of 16 - 18 years causes many deviant actions, such as cyber bullying. Especially social media that has a comment feature that makes it easy for teenagers to upload bad comments to victims. This research uses descriptive quantitative methods using regression analysis. In this test, it was found that the contribution of emotion regulation as a negative predictor of cyber bullying was F = 180.041, p < 0.01, and R² = 0.643. This shows that R² has a contribution of 64.3% to cyber bullying. This means that the higher the emotion regulation, the lower the cyber bullying behavior. Suggestions for future research are to investigate the long-term outcomes and sustainability of this intervention in reducing incidents of cyberbullying and improving emotion regulation skills.